Cyborgs from Fiction to Reality: Marginalized Other or Privileged First? - Aneta Stojnić (Identities, 2013)
In this paper I will offer an analysis of cyber technology, cyberspace and cyborg from its appearance in fiction to its contemporary realizations, in order to show symbolic place of cyborg has changed, in the light of contemporary power relations. I will focus on the cyborg figure in literature and film, mainly the cyberpunk genre characteristic for fictionalization of the relations between individual, society and technology.